Overview of household waste management in Sama Subur Village, North Konawe - Paridah Paridah; Hartati Bahar; Firza Azzahra (PT WIM Solusi Prima, 2026)
Household waste management remains one of the environmental health problems commonly found in rural communities. Improper waste management can cause environmental pollution and increase the risk of public health problems. This study aimed to describe household waste management in Sama Subur Village, Motui District, North Konawe Regency. This research was a descriptive study with a quantitative approach. The study was conducted in January 2026 involving 46 household heads selected using a total sampling technique. Data were collected through interviews using structured questionnaires and observation sheets. The variables studied included the availability of household trash bins, separation of organic and inorganic waste, main methods of waste disposal, frequency of waste disposal, barriers to waste management, and disturbances caused by waste. Data were analyzed descriptively and presented in frequency distribution tables and percentages. The results showed that most respondents used open trash bins (78.3%), never separated organic and inorganic waste (76.1%), and disposed of waste by burning (84.8%). Most respondents disposed of waste daily (54.3%). The main barrier to waste management was the absence of waste collection services (60.9%). Most respondents reported no disturbances caused by waste (82.6%). The study concluded that household waste management in Sama Subur Village is still not optimal and requires improved facilities and community education regarding proper and healthy waste management.